Aplicação do kit completo para minimizar a interrupção do fluxo de trabalho: making-do e trabalho inacabado - Soares, Klisman Mateus de Andrade; Pinto, Maria Gabriela de Almeida; Santos, Tauane Barbosa Dos; Santos, Débora De Gois; Michelan, Denise Conceição De Gois Santos; Santos, Paulo Ricardo Ramos (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The current scenario of the construction sector has several peculiarities regarding the standardization and development of processes. These unusual features are not always favorable and resulting in rework and improvisations in the construction site, which leads to disruption of the process. One solution is to provide the complete kit, to avoid waste by making-do and work in progress. The aim is to identify which categories of best practice are most valued by engineers, in search of continuity of the work, by applying the complete kit. The method includes the elaboration of a framework of managerial actions; information about the importance of the adoption of best practices, through the application of questionnaires based in the theoretical framework. As a result, managers attributed "great importance" to the managerial actions of the categories: worker protection, work conference, process protection, and access. It is concluded that the managers concentrate on the work at the production site, rather than actions for work preparation, project and schedule.